HYGIENIC JUSTIFICATION OF NOISE PROTECTION MEASURES IN THE CITY OF TASHKENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper examines the impact of urban noise on the health of the Tashkent population and justifies a set of noise protection measures from an environmental health perspective. An assessment of the acoustic environment in various functional zones of the city (residential areas, highways, and industrial zones) was conducted, identifying the main sources of noise pollution and their contribution to the overall sound level. Based on an analysis of the obtained data, excesses of maximum permissible noise levels were determined and a hygienic assessment of the potential risk to public health was provided. Effective noise protection measures have been proposed and substantiated, including urban planning, architectural design, engineering, and organizational/administrative solutions. Particular attention is paid to the use of green spaces, noise barriers, rational zoning, and traffic flow optimization. The study's findings support the need for a comprehensive approach to reducing noise pollution in Tashkent and the implementation of hygienically sound measures at the design and operation stages of urban infrastructure.